CaM Kinases: From Memories to Addiction - Müller, Christian P.; Quednow, Boris B.; Lourdusamy, Anbarasu; Kornhuber, Johannes; Schumann, Gunter; Giese, Peter (Trends in Pharmacological Sciences, 2016)
Drug addiction is a major psychiatric disorder with a neurobiological basis that is still insufficiently understood. Initially, non-addicted, controlled drug consumption and drug instrumentalization are established. They comprise highly systematic behaviours acquired by learning and the establishment of drug memories. Ca(2+)/calmodulin-dependent protein kinases (CaMKs) are important Ca(2+) sensors translating glutamatergic activation into synaptic plasticity during learning and memory formation. Here we review the role of CaMKs in the establishment of drug-related behaviours in animal models and in humans. Converging evidence now shows that CaMKs are a crucial mechanism of how addictive drugs induce synaptic plasticity and establish various types of drug memories. Thereby, CaMKs are not only molecular relays for glutamatergic activity but they also directly control dopaminergic and serotonergic activity in the mesolimbic reward system. They can now be considered as major molecular pathways translating normal memory formation into establishment of drug memories and possibly transition to drug addiction.
EVALuna2:23777